2019
DOI: 10.1017/s136898001900199x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the modelled impacts on CVD mortality if attainment of public health recommendations was achieved in metropolitan and rural Australia

Abstract: Objective:To (i) determine the proportion of deaths from CVD that could be avoided in both rural and metropolitan Australia if public health recommendations were met; (ii) assess the impact on the rural CVD mortality; and (iii) determine if policy priorities should be different by rurality for CVD prevention.Design:A macro-simulation modelling study of population data. Population, risk factor and CVD death data stratified by rurality were analysed using the Preventable Risk Integrated Model. The baseline scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
(30 reference statements)
1
28
0
Order By: Relevance
“…Dietary risks and obesity contributed to almost half of the burden of disease attributed to exposure to risk factors 3 . People who live in rural and remote areas of Australia experience more significant impact from diet‐related chronic diseases, with higher rates of overweight and obesity, cardiovascular disease, type 2 diabetes, high blood pressure, and chronic kidney disease, than their metropolitan counterparts 2,4 . An Australian Institute of Health and Welfare report in 2019 showed that only 1 in 10 people living outside major cities reported meeting requirements for vegetable intake, and fewer Australians living in rural areas meet fruit recommendations than their metropolitan counterparts, 2 presenting an opportunity target for policy and interventions seeking to decrease preventable disease burden in rural areas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dietary risks and obesity contributed to almost half of the burden of disease attributed to exposure to risk factors 3 . People who live in rural and remote areas of Australia experience more significant impact from diet‐related chronic diseases, with higher rates of overweight and obesity, cardiovascular disease, type 2 diabetes, high blood pressure, and chronic kidney disease, than their metropolitan counterparts 2,4 . An Australian Institute of Health and Welfare report in 2019 showed that only 1 in 10 people living outside major cities reported meeting requirements for vegetable intake, and fewer Australians living in rural areas meet fruit recommendations than their metropolitan counterparts, 2 presenting an opportunity target for policy and interventions seeking to decrease preventable disease burden in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Diet plays a role in rural health inequalities, such as disparities in cardiovascular disease 4,5 . A recent study suggests that the gap in ischaemic heart disease mortality between rural and metropolitan Australia could be reduced by almost half if rural Australians were able to meet recommendations for diet, reduce alcohol, meet activity guidelines, and cease smoking tobacco 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the 2017–18 National Health Survey, rural‐dwelling Australians were more likely to consume sugar‐sweetened drinks daily (14%) than their counterparts in major cities (8%), while less than 10% of rural people met guidelines for vegetable intake 3 . Modelling studies indicate that Australians meeting dietary guidelines would reduce cardiovascular disease mortality by as much as 50% in rural areas, and reduce inequities in rates between rural and metropolitan areas 4 …”
mentioning
confidence: 99%